Anne of Avonlea - Montgomery, L. M. (Lucy Maud), 1874-1942. (New York : Puffin, 1994)
In this sequel to Anne of Green Gables, the teenage Anne Shirley becomes a school teacher in a small village on Prince Edward Island.
"Complete and unabridged"--Cover p. [4].
7.6
5-8
Keywords: Orphans -- Fiction; Schools -- Fiction; Shirley, Anne (Fictitious character) -- Fiction; Teachers -- Fiction; Orphans -- Fiction; School stories; Shirley, Anne (Fictional character) -- Fiction; Teachers -- Fiction; Prince Edward Island -- Fiction; Prince Edward Island -- Fiction